Can you help me get started on this proof?

I'm having trouble on where to begin with this proof. I'm pretty sure it is a valid argument, since I tried to come up with a counter-example but couldn't. I will use the symbol ~ to stand for "not", since I don't know how to make the "not" symbol online.

Directions: Derive ~Z -> ~Y

(1) ~X -> Y

(2) ~X -> Z

-------------------

(3) ~Z -> ~(~X).......... (1) Contrapositive

I think I should start with the contrapositive, but I have no clue where to go from here. Any help would be appreciated :)